Commentary on Vorobjov et al., "Comparison of injection drug users who obtain syringes from pharmacies and syringe exchange programs in Tallinn, Estonia" - Werb Daniel; Wood Evan (BMC, 2009)
Abstract Recent data suggest that globally, between 5% and 10% of all new HIV cases are the result of unsafe injecting practices, and experts agree that reducing these practices is key to tackling the spread of HIV. And yet, despite the overwhelming evidence that providing sterile syringes to injection drug users (IDU) through syringe exchange programs (SEPs) or other means is an effective way of reducing HIV transmission among high-risk subpopulations, IDU in most settings still do not have access to sterile injecting equipment or if they do, access remains too restricted to effectively reduce the risk of HIV transmission. Vorobjov and colleagues have presented in this journal an interesting and timely study from Estonia comparing individuals who obtain syringes from SEPs and those who obtain syringes from pharmacies. As the authors point out, Estonia faces an unacceptably high HIV incidence rate of 50 new HIV cases per 100,000, this rate driven primarily by injection drug use. As such, the authors argue that Estonia's SEP network does not have the capacity to serve a growing IDU population at risk of transmitting HIV and pharmacy dispensation of clean syringes may be one potential approach to decreasing syringe sharing among high-risk injectors. It may be overly optimistic to consider the impact of higher threshold interventions such as pharmacy-based SEPs, given that IDU populations that engage in HIV risk behaviours such as syringe sharing are often hidden or hard to reach. Despite the need for a cautious approach, however, the findings presented by Vorobjov et al. may chart one potential course towards a more comprehensive societal response to reducing the health harms associated with injection drug use.